"A decade's worth of work in a matter of days": The journey to telehealth for the whole population in Australia. (July 2021) - Hall Dykgraaf, Sally; Desborough, Jane; de Toca, Lucas; Davis, Stephanie; Roberts, Leslee; Munindradasa, Ashvini; McMillan, Alison; Kelly, Paul; Kidd, Michael
Abstract: Introduction: Internationally the COVID-19 pandemic has triggered a dramatic and unprecedented shift in telehealth uptake as a means of protecting healthcare consumers and providers through remote consultation modes. Early in the pandemic, Australia implemented a comprehensive and responsive set of policy measures to support telehealth. Initially targeted at protecting vulnerable individuals, including health professionals, this rapidly expanded to a "whole population" approach as the pandemic evolved. This policy response supported health system capacity and community confidence by protecting patients and healthcare providers; creating opportunities for controlled triage, remote assessment and treatment of mild COVID-19 cases; redeploying quarantined or isolated health care workers (HCWs); and maintaining routine and non-COVID healthcare. Purpose: This paper provides a review of the literature regarding telephone and video consulting, outlines the pre-COVID background to telehealth implementation in Australia, and describes the national telehealth policy measures instituted in response to COVID-19. Aligned with the existing payment system for out of hospital care, and funded by the national health insurance scheme, a suite of approximately 300 temporary telehealth Medicare-subsidised services were introduced. Response to these initiatives was swift and strong, with 30.01 million services, at a cost of AUD $1.54 billion, claimed in the first six months. Findings: This initiative has been a major policy success, ensuring the safety of healthcare consumers and healthcare workers during a time of great uncertainty, and addressing known financial risks and barriers for health service providers. The risks posed by COVID-19 have radically altered the value proposition of telehealth for patients and clinicians, overcoming many previously encountered barriers to implementation, including willingness of clinicians to adopt telehealth, consumer awareness and demand, and the necessity of learning new ways of conducting safe consultations. However, ensuring the quality of telehealth services is a key ongoing concern. Conclusions: Despite a preference by policymakers for video consultation, the majority of telehealth consults in Australia were conducted by telephone. The pronounced dominance of telephone item numbers in early utilisation data suggests there are still barriers to video-consultations, and a number of challenges remain before the well-described benefits of telehealth can be fully realised from this policy and investment. Ongoing exposure to a range of clinical, legislative, insurance, educational, regulatory, and interoperability concerns and solutions, driven by necessity, may drive changes in expectations about what is desirable and feasible – among both patients and clinicians.